2019
DOI: 10.7759/cureus.5638
|View full text |Cite
|
Sign up to set email alerts
|

Use of Autologous Blood Components in Lymphedema Treatment: A Systematic Review

Abstract: The main benefit of autologous therapies is its easier obtention and relatively lower concerns regarding ethical implications and patient safety. We conducted a systematic review of publications assessing the potential use of blood components (lymphocytes, red blood cells (RBCs), platelet-rich plasma (PRP)) as targeted therapy in the treatment of lymphedema. We hypothesized that blood components could be used as targeted therapy in the lymphedema treatment. We also conducted a comprehensive, systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The literature on the pathogenesis and treatment of lymphedema has increased considerably over the years [26][27][28], but current options for treatment of lymphedema such as physiologic surgeries (lymphaticovenous bypass and lymph node transfer) still have unpredictable outcomes [29]. In this systematic literature review, we have shown the existence of promising evidence supporting the potential of ADSCs in lymphatic tissue engineering and regeneration.…”
Section: Discussionmentioning
confidence: 84%
“…The literature on the pathogenesis and treatment of lymphedema has increased considerably over the years [26][27][28], but current options for treatment of lymphedema such as physiologic surgeries (lymphaticovenous bypass and lymph node transfer) still have unpredictable outcomes [29]. In this systematic literature review, we have shown the existence of promising evidence supporting the potential of ADSCs in lymphatic tissue engineering and regeneration.…”
Section: Discussionmentioning
confidence: 84%